Assessment of aerobic and anaerobic thresholds in five different technique specific incremental treadmill tests in cross country skiers - Monahan, Kristen (2016)
The use of incremental tests to exhaustion is widely accepted in the field of exercise physiology in the assessment of athletes. These tests which can measure a number of physiological parameters can help coaches and athletes optimize training. Blood lactate concentrations (bLa) corresponding to heart rate (HR) provides insight on the athlete’s aerobic threshold (AerT) and anaerobic threshold (AnT). Cross country skiing is a sport where the selection of technique may influence the HR at which AerT and AnT occurs, eliciting higher bLa corresponding to lower HR depending on technique. Because of this, laboratory testing is crucial to provide coaches and athletes with the necessary information to help optimize training. Research has compared two to three techniques in cross country skiing in regards to variations in HR at AnT, nowhere has there been a study which has tried comparing AerT and AnT as well as maximal oxygen consumption (VO2max) in 5 different techniques (Nordic walking, double poling, diagonal striding, V1, and V2 skate). Therefore, the purpose of this study is to determine the AerT and AnT from a physiological examination of bLa, HR and VO2max. Ten national level skiers completed five incremental treadmill tests to exhaustion. Results were analyzed with both genders and split by genders. In all groups tested significant differences were found, DP being the main technique affected, lower HRs were observed in DP at AerT and AnT compared to the other techniques. VO2max in women’s DP were significantly lower than all techniques. The results demonstrated technique specific laboratory treadmill tests can be used to evaluate HR training zones for athletes as well as individuals VO2max. It is recommended to choose a test incorporating whole body musculature, (NW, DS or V2), and a test that represents upper body musculature, (DP or V1). In this way, two tests can be compared that will provide information on training intensities, and possible differences between whole and upper body musculature. With this information the coaches are able to help guide the athlete in future training goals for optimal performance. Results between different techniques at group levels should be used with discretion, inter-individual differences exist among athletes.